2010
DOI: 10.1007/s10661-010-1785-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in Nile tilapia (Oreochromis niloticus) and armored catfish (Pterygoplichthys anisitsi) exposed to diesel oil

Abstract: Considering that diesel oil is one of the most common aquatic contaminants, we compare the oxidative stress between two species of fish with different habitats (Pterygoplichthys anisitsi, benthic and Oreochromis niloticus, nektonic) exposed to diesel oil. Malondialdehyde concentrations (MDA) and the activities of ethoxyresorufin-O-deethylase (EROD), glutathione S-transferase (GST), catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase were all analyzed in the fishes' livers and gills after 2 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 44 publications
2
20
0
2
Order By: Relevance
“…In the present study, the increase in SOD activity in exposed zebrafish tissue was possibly related to increased oxidative stress caused by OP (MAL, ATR) and heavy metal (Cd), and this was consistent with the study of [38], who inquired into the changes of SOD activity caused by chlorpyrifos exposure in adult Oreochromis niloticus. Nogueira, et al [39] found higher SOD activity in gills of two species, Nile tilapia (Oreochromis niloticus) and armoured catfish (Pterygoplichthys anisitsi) exposed to diesel oil, and referred to the elevated SOD activity in their study may be to protect cells against oxidative damage. The rise of CAT activities in zebrafish brain and muscle observed in the present study may be a response to H 2 O 2 production catalysed by activated SOD, because CAT is involved in the detoxification of H 2 O 2 in water.…”
Section: Discussionmentioning
confidence: 85%
“…In the present study, the increase in SOD activity in exposed zebrafish tissue was possibly related to increased oxidative stress caused by OP (MAL, ATR) and heavy metal (Cd), and this was consistent with the study of [38], who inquired into the changes of SOD activity caused by chlorpyrifos exposure in adult Oreochromis niloticus. Nogueira, et al [39] found higher SOD activity in gills of two species, Nile tilapia (Oreochromis niloticus) and armoured catfish (Pterygoplichthys anisitsi) exposed to diesel oil, and referred to the elevated SOD activity in their study may be to protect cells against oxidative damage. The rise of CAT activities in zebrafish brain and muscle observed in the present study may be a response to H 2 O 2 production catalysed by activated SOD, because CAT is involved in the detoxification of H 2 O 2 in water.…”
Section: Discussionmentioning
confidence: 85%
“…A toxicidade do óleo diesel para juvenis de tilápia já foi relatada por NOGUEIRA et al (2011), que constataram a exposição dos juvenis de O. niloticus nas diluições de 0,01 e 0,05% por sete dias, verificando mortalidade de 100% dos peixes no sexto dia de experimento para a maior diluição testada. Já SCHEIN et al (2009), realizando ensaios crônicos com alevinos de truta-arco-íris (Oncorhynchus Mykiss) e usando duas diluições da fração solúvel em água de óleo diesel (0,01 e 1%) ao longo de nove dias, determinaram concentração média de 0,05%.…”
Section: Resultado E Discussãounclassified
“…Já SCHEIN et al (2009), realizando ensaios crônicos com alevinos de truta-arco-íris (Oncorhynchus Mykiss) e usando duas diluições da fração solúvel em água de óleo diesel (0,01 e 1%) ao longo de nove dias, determinaram concentração média de 0,05%. No presente estudo, a concentração letal média a 50% encontrada foi maior que os achados de NOGUEIRA et al (2011) e SCHEIN et al (2009, com mortalidade de 100% em menos de 24 horas.…”
Section: Resultado E Discussãounclassified
“…Hence, accumulation of metals in the fish tissues affects their physiology. Several studies have reported alteration in level of protein, lipid, carbohydrate, and activities of different enzymes in the fish in response to different xenobiotics (Palanisamy et al 2011;Yousafzai and Shakoori 2011;Yacoub and Gad 2012;Liebel et al 2011;Nogueira et al 2011). Since they act as biomarker of the health of fish, their assessment is very important to evaluate the effect of pollution on the fish health.…”
Section: Introductionmentioning
confidence: 99%